Isomer-specific molecular interaction of cationic glucosamine with benzoate and phthalates: individual stabilities of unresolvable-isomer complexes detected by NMR titration. Issue 10 (2nd October 2020) - D-Yañez, Sheyla; Soberanes, Yedith; Navarro, Rosa Elena; Virués, Claudia; Inoue, Motomichi
ABSTRACT: Some biogenic compounds undergo conformational isomerism, and the isomers may interact distinctively with other substances to form molecular complexes individually with different stabilities. In the present work, such molecular interaction specific to isomers was confirmed for the complexation of cationic glucosamine anomers with benzoate and phthalate anions. The individual stability constants of the anomer complexes were determined by tracing 1 H NMR shifts of each anomer in titration with the appropriate carboxylate. In the complexes of benzoate, phthalate and terephthalate, the binding forces in the β-anomer complexes are two to five times as strong as those of the corresponding α-anomer complexes. The formulae of titration curves for determining individual stabilities have been developed in a generalised form to be applicable to the complexation of other unresolvable isomers with different compositions. Graphical abstract: